Japanese radiological technologists’ perceptions and interest in disaster medicine and radiation emergency medicine - Tsujiguchi, Takakiyo; Naraoka, Masato; Koiwa, Tomoki; Yamanouchi, Kanako; Ito, Katsuhiro (Frontiers in Public Health, 2024)
Since the Fukushima Daiichi Nuclear Power Plant accident in Japan, there has been a growing demand for radiological technologists to play active roles in radiation emergency medicine. This study administered a questionnaire survey to determine radiological technologists’ experience, interest, and confidence in disaster medicine and radiation emergency medicine as well as their educational needs, particularly regarding radiation emergency medicine. Findings showed that less than 10% of radiological technologists working at nuclear emergency core hospitals and nuclear emergency medical cooperative institutions for nuclear disaster medical care had studied disaster medicine, regardless of their affiliation, age, or years of service, and that they lacked educational experience. However, they showed interest in general disasters and emergency medicine, and all aspects necessary for the treatment of injured and sick patients in nuclear disasters, such as dosimetry and radiation control, and were willing to learn through online formats, such as e-learning, to expand their learning opportunities. This research seeks to promote a positive perception of disaster and radiation emergency medical education among radiological technologists.